Matching Regulatory Design to Country Circumstances : The Potential of Hybrid and Transitional Models - Eberhard, Anton (World Bank, Washington, DC, 2012)
Developing countries attempting to implement the standard model of independent regulation have encountered many problems and challenges. These may arise when a regulatory system is incompatible with the country's regulatory commitment and institutional and human resource endowment. Selecting from a menu of regulatory options to create a hybrid model -- one that best fits a country's own circumstances and challenges -- can improve regulatory performance.